2019
DOI: 10.1039/c9tc02967b
|View full text |Cite
|
Sign up to set email alerts
|

A ternary ZnO/ZnS/MoS2 composite as a reusable SERS substrate derived from the polyoxomolybdate/ZIF-8 host–guest framework

Abstract: A ternary nanocomposite of ZnMoNCs containing ZnO, ZnS and MoS2 has been synthesized by a facile strategy derived from polyoxometalate and ZIF-8, which shows high SERS activity by increased adsorption sites and synergistically improved charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…[247][248][249][250] For example, in a proof-of-concept demonstration, Liu, Gao, et al designed photocatalytically active ternary ZnO/ZnS/MoS 2 nanocomposites, as shown in Figure 17D, which could be used as reusable substrates for SERS. 251 The nanocomposites were synthesized through in-situ chemical growth using phosphomolybdic acid hydrate (PMo 12 )@zeolitic imidazolate frameworks-8 (ZIF-8) as the precursor. Importantly, forming the nanocomposites via this approach allowed nanoscale contact points between the ZnO, ZnS and MoS 2 in the nanocomposites to be generated with higher efficiency compared to physically mixing the individual components which is significant for achieving strong SERS and photocatalytic activity (Figure 17E).…”
Section: Photocatalytic Regenerationmentioning
confidence: 99%
“…[247][248][249][250] For example, in a proof-of-concept demonstration, Liu, Gao, et al designed photocatalytically active ternary ZnO/ZnS/MoS 2 nanocomposites, as shown in Figure 17D, which could be used as reusable substrates for SERS. 251 The nanocomposites were synthesized through in-situ chemical growth using phosphomolybdic acid hydrate (PMo 12 )@zeolitic imidazolate frameworks-8 (ZIF-8) as the precursor. Importantly, forming the nanocomposites via this approach allowed nanoscale contact points between the ZnO, ZnS and MoS 2 in the nanocomposites to be generated with higher efficiency compared to physically mixing the individual components which is significant for achieving strong SERS and photocatalytic activity (Figure 17E).…”
Section: Photocatalytic Regenerationmentioning
confidence: 99%
“…91 Interestingly, ternary nanocomposites made of ZnO, ZnS and MoS2 were reported to provide higher SERS sensitivity and stability than their mono-or bi-component counterparts. 92 The porous structure of these ternary materials allows increasing the number of adsorption sites. In addition, they exhibit self-cleaning properties upon UV irradiation and can be reused without loss of activity for more than 5 detection cycles.…”
Section: D Transition Metal Chalcogenidesmentioning
confidence: 99%
“…Indeed, nonstoichiometric WSe 2− x ( x = 0–0.08) prepared by bombarding stoichiometric WSe 2 with an ion beam, provided a 40‐fold increase of the enhancement factor compared to pristine WSe 2 (Liu et al, 2018). Interestingly, ternary nanocomposites made of ZnO, ZnS, and MoS 2 were reported to provide higher SERS sensitivity and stability than their mono‐ or bi‐component counterparts (Yin et al, 2019). The porous structure of these ternary materials allows increasing the number of adsorption sites.…”
Section: Non‐plasmonic Substratesmentioning
confidence: 99%
“…They finally realized that the dipole moment of an MBA molecule could significantly influence the charge-transfer mechanism and speed between the TiO 2 and CdS NPs fields. 73 Yin et al 74 also synthesized a novel and smart SERS substrate using a ternary nanocomposite containing ZnO, ZnS, and MoS 2 (ZnMoNCs) by a chemical combination method. They first employed PMo 12 and ZIF-8 as Mo and Zn sources, respectively, to fabricate PMo 12 @ZIF-8 precursors before transforming them into ternary ZnO, ZnS, and MoS 2 -based nanocomposites by sulfuration and carbonization (Figure 4c).…”
Section: ■ Sers and Its Working Mechanismmentioning
confidence: 99%